Synergetics: A Historical Analysis of the Ideas of Self-Organization - Rizaev Ilhom (Penerbit Jurnal Indonesia, 2024)
The article comprehensively analyses the history of the concept of self-organization and its philosophical foundations, and also examines the scientific, mythological and philosophical sources of the emergence of the idea of ​​self-organization. The author examined the evolution of ideas about chaos and order in various worldview systems (mythology, Western and Eastern philosophy) and explored their place in human thinking and the development of society.